The Role of Character Education in the Madrasah Curriculum: A Study on Students' Social Behavior - Abdullah (Islamic Journal of Teaching and Learning, 2025)
Character education in madrasas is an important component in shaping students' social behavior, especially in the modern era which is full of social challenges. Character values such as empathy, responsibility, and cooperation play a significant role in improving the quality of students' social interactions inside and outside the school environment. This study aims to analyze the role of character education in the madrasah curriculum on the formation of positive social behavior in students. This study uses a quantitative approach with a descriptive survey design. Data was obtained from 150 madrasah students in Indonesia through a questionnaire that measured the level of implementation of character education and its impact on social behavior. The analysis was carried out with a correlation test to see the relationship between the intensity of character education and students' social behavior. The results of the study show that character education has a significant influence on improving students' social behavior, such as empathy and responsibility. Students who receive intensive character education show better self-control and a more empathetic attitude towards their peers. In addition, these findings reveal challenges in the implementation of character education, such as limited time and lack of training for teachers. The implication of this study is the need for the development of more intensive character education programs and training support for teachers to maximize the positive impact of character education in madrassas.